Hubungan Antara Iklim Organisasi dengan Kepuasan Kerja Karyawan Toko Retail Indomaret di Wilayah Sidoarjo - Ningtita, Nur Arifa Wahyu; Mariyati, Lely Ika (Web of Scientist International Scientific Research Journal, 2024)
A company is expected to create a comfortable and conducive working atmosphere so that employee job satisfaction can increase and create a good organizational climate. This is the background of this research. This study aims to determine "The Relationship between Organizational Climate and Job Satisfaction of Indomaret Retail Store Employees in the Sidoarjo Region". The X variable is Organizational Climate and the Y variable is Job Satisfaction. The sample in this study were Indomaret retail store employees in Sidoarjo, which are located in 3 sub-districts, namely, Porong, Tanggulangin, and Candi with a total of 191 employees. The cluster sampling technique was used in this study with a scale-building model, namely the job satisfaction scale and the organizational climate scale. On the job satisfaction scale it was found that the validity value moved from 0.082 to 0.599 and the results of the job satisfaction scale reliability test obtained the Alpha Cronbach's reliability coefficient of 0.902 with a total of 34 valid items. While the organizational climate scale found validity values ​​that moved from 0.065 to 0.391 and the results of the organizational climate scale reliability test obtained Alpha Cronbach's reliability coefficient of 0.916 with a total of 34 valid items. The method used in this research is descrptive qualitative with the help of SPSS 17 for Windows. The results of data analysis on the organizational climate scale with the job satisfaction scale obtained rxy = 0.694 with a sig. 0.000 <0.050 which means the hypothesis can be interpreted that there is a significant relationship between organizational climate and job satisfaction.